PERK Pathway Activation Promotes Intracerebral Hemorrhage Induced Secondary Brain Injury by Inducing Neuronal Apoptosis Both in Vivo and in Vitro - Meng, Chengjie; Zhang, Juyi; Dang, Baoqi; Li, Haiying; Shen, Haitao; Li, Xiang; Wang, Zhong (Frontiers in Neuroscience, 2018)
The protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK) signaling pathway was reported to exert an important role in neuronal apoptosis. The present study was designed to investigate the roles of the PERK signaling pathway in the secondary brain injury (SBI) induced by intracerebral hemorrhage (ICH) and its potential mechanisms. Sprague–Dawley rats were used to establish ICH models by injecting autologous blood (100 μl), and cultured primary rat cortical neurons were exposed to oxyhemoglobin (10 μM) to mimic ICH in vitro. The PERK antagonist, GSK2606414, and inhibitor of eukaryotic translation initiation factor 2 subunit α (eIF2α) dephosphorylation, salubrinal, were used to study the roles of PERK signaling pathway in ICH-induced SBI. Our results showed that the protein levels of p-eIF2α and ATF4 were upregulated following ICH, peaking at 48 h. Application of GSK2606414 reversed this increase in vivo and in vitro, thereby preventing ICH-induced neuronal apoptosis. On the contrary, salubrinal inhibited the dephosphorylation of eIF2α, resulting in the elevation of p-eIF2α, which could activate downstream of PERK signaling and induce neuronal apoptosis and necrosis following ICH in vitro and in vivo. Thus, PERK signaling pathway plays an important role in ICH-induced apoptosis and blocking its activation has neuroprotective effects that alleviates SBI, suggesting that targeting this pathway could be a promising therapeutic strategy for improving patient outcome after ICH.